2010
DOI: 10.1128/jcm.01948-09
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Based Identification of Filamentous Basidiomycetous Fungi from Clinical Specimens: a Cautionary Note

Abstract: The species-level identification of sterile and/or arthroconidium-forming filamentous fungi presumed to be basidiomycetes based upon morphological or physiological features alone is usually not possible due to the limited amount of hyphal differentiation. Therefore, a reliable molecular approach capable of the unambiguous identification of clinical isolates is needed. One hundred sixty-eight presumptive basidiomycetes were screened by sequence analysis of the internal transcribed spacer (ITS) and D1/D2 ribosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 29 publications
5
75
0
1
Order By: Relevance
“…Unique sequences were identified and compared with a fungal reference database, and those not assigned to Fungi (6.76% of all unique sequences, 5.75% of reads) were removed. While there will likely be differential genetic diversity within fungal species, empirical studies suggest that multiple species of Ascomycota and Basidiomycota differ by less than 2% at the 26S rDNA gene (Kurtzman and Robnett, 2003;Romanelli et al, 2010). Thus, the remaining 486 279 reads were aligned against a fungal reference database and clustered into groups that share 498% identity.…”
Section: Discussionmentioning
confidence: 99%
“…Unique sequences were identified and compared with a fungal reference database, and those not assigned to Fungi (6.76% of all unique sequences, 5.75% of reads) were removed. While there will likely be differential genetic diversity within fungal species, empirical studies suggest that multiple species of Ascomycota and Basidiomycota differ by less than 2% at the 26S rDNA gene (Kurtzman and Robnett, 2003;Romanelli et al, 2010). Thus, the remaining 486 279 reads were aligned against a fungal reference database and clustered into groups that share 498% identity.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates the relevance of NSMs in a clinical context. Previous series on the molecular characterization of NSMs did not consider the clinical backgrounds of patients (9,37). However, the authors of both of those series indicated that NSMs isolated from otherwise sterile sites could be potential pathogens (9,37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous series on the molecular characterization of NSMs did not consider the clinical backgrounds of patients (9,37). However, the authors of both of those series indicated that NSMs isolated from otherwise sterile sites could be potential pathogens (9,37). Finally, patients with chronic pulmonary diseases for whom basidiomycetes are isolated from the lower respiratory tract should be thoroughly evaluated to rule out an allergic or invasive disease, and the basidiomycetes should not just be ignored as possible contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…Template DNA was isolated from PDA plates as described previously (12). PCR was performed using template DNA and primers ITS1 and NL4 to amplify a single contig containing the internal transcribed spacer (ITS) and D1-D2 regions, and the amplified material was then sequenced on both strands with primers ITS1, ITS4, NL1, and NL4 at the UTHSCSA Advanced Nucleic Acids Core Facility (12). The ITS and D1-D2 sequences were then used to search the GenBank database at the NCBI website (http://blast.ncbi .nlm.nih.gov/Blast.cgi) using the BLASTn algorithm.…”
mentioning
confidence: 99%